Smart battery charger for electric mobility in smart grids - Monteiro, Vítor Duarte Fernandes (2012)
In this paper is presented the development of a smart batteries charger for Electric Vehicles (EVs) and Plug-in Hybrid Electric Vehicles (PHEVs), aiming their integration in Smart Grids. The batteries charging process is controlled by an appropriate control algorithm, aiming to preserve the batteries lifespan. The main features of the equipment are the mitigation of the power quality degradation and the bidirectional operation, as Grid-to-Vehicle (G2V) and as Vehicle-to-Grid (V2G). During the charging process (G2V), the consumed current is sinusoidal and the power factor is unitary. Along the discharging process (V2G), when the equipment allows delivering back to the electrical power grid a small amount of the energy stored in the batteries, the current is also sinusoidal. The V2G mode of operation will be one of the main features of the Smart Grids, both to collaborate with the electrical power grid to increase stability, and to function as a distributed Energy Storage System (ESS). The functioning of the smart batteries charger is shown through simulation and experimental results, both during the charging (G2V) and the discharging (V2G) modes of operation. Also in this paper are shown and briefly described the roles of the key concepts related with the Smart Grids in terms of Systems and Functional Areas, Power Electronics Systems, and Electric Mobility.